Turkey’s “New” Middle East or More of the Same - Ergül Jorgensen, Feride Asli (The Copernicus Journal of Political Studies, 2018)
Turkey’s Middle East policy has been changed a lot in time but the most dramatic one has happened during the reign of the AKP government. As the political Islam tendency in Turkey has evolved, the economic, political and cultural relations with the Middle East have developed in parallel. Besides, the Turkish democracy, which seems to solve its problems with Islam, is shown by some people as a “model” for the Middle Eastern countries. It is a fact that the recent Gezi protests in Turkey constitute some doubts about the success of this model but the impact of AKP’s new foreign policy on the Middle Eastern politics is clear. With the “zero problems policy” and the “new activism” era in Turkish foreign policy, Turkey has focused on the Middle East more than ever. However, to evaluate this change as a complete turn from Turkey’s centuryold westernization and a shift in its identity would be a misreading of the developments. In fact, this change could be interpreted as another phase in its strategic foreign policy enriched with an opening to the East. In this context, this article tries to discuss the new orientation of Turkey upon old grounds in the Middle East according to its new focus between the regional dynamics and global actors. Full text: http://bazhum.muzhp.pl/czasopismo/589/?idno=14763